2013
DOI: 10.1177/1457496913489085
|View full text |Cite
|
Sign up to set email alerts
|

Wide excision in right-sided colon cancer is associated with decreased survival

Abstract: Background and Aims: Nodal involvement is the most important prognostic factor in colon cancer. Although theoretically appealing, it is not known if wider mesenteric excision improves the oncological result. The aim of this retrospective study was to investigate whether wider mesenteric excision yields a superior oncological result. Material and Methods: Depending on the resection length, 333 cases of locally radical right-sided hemicolectomies due to adenocarcinoma were compared for perioperative morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The worse overall survival of colon cancer is most likely multi‐factoral. Recently complete mesocolic excision (CME) and high ligation of the artery have been emphasized although data are opposing . Furthermore, a larger proportion of colonic resections are still performed by General Surgeons where as rectal cancer is almost exclusively managed by Colorectal specialists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worse overall survival of colon cancer is most likely multi‐factoral. Recently complete mesocolic excision (CME) and high ligation of the artery have been emphasized although data are opposing . Furthermore, a larger proportion of colonic resections are still performed by General Surgeons where as rectal cancer is almost exclusively managed by Colorectal specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Recently complete mesocolic excision (CME) and high ligation of the artery have been emphasized although data are opposing. 8,9 Furthermore, a larger proportion of colonic resections are still performed by General Surgeons where as rectal cancer is almost exclusively managed by Colorectal specialists. In the last cohort there was a tendency to improved survival for stage I and II disease in colon cancer if operated by a colorectal surgeon which underlines the importance of sub-specialization.…”
Section: Discussionmentioning
confidence: 99%
“…There is no rationale in performing an extended resection if a more limited resection is adequate regarding survival and oncological results. In a previous retrospective study our group has shown an increased long‐term mortality associated with wider bowel resection in right‐sided colon cancer .…”
Section: Introductionmentioning
confidence: 89%
“…Adjuvant chemotherapy in stages II and III of colon cancer has shown to increase survival by 5-15% in randomized trials [21]. Nevertheless, complete mesocolic excision and central vascular ligation have been emphasized recently, although data are opposing [22][23][24].…”
Section: Discussionmentioning
confidence: 99%